Minimizing the Influence of Cogging Torque on Motor Performance of PM Synchronous Machines for Elevator Applications - Polat, Mehmet; Akyun, Yakup; Nory, Hayatullah (Springer Heidelberg, 2022)
Low speed and high torque permanent magnet synchronous motors are used in elevator applications. In these motors, the cogging torque causes negative effects. The cogging torque is a magneto-static effect caused by the change in magnetic attractiveness and repulsiveness surrounding the rotor magnets during the rotation of the rotor itself. This torque causes ripple and noise hence, it must be reduced especially at small loads and low speeds. For this reason, the focus of this study is to design a Permanent Magnet Synchronous Motor (PMSM) with high efficiency, power density and torque/ volume rate, and with reduced undesired cogging torque. Designed motor in aforementioned criteria has been analyzed with different skew lengths to reduce the cogging torque. The effects of the skew on the motor torque, cogging torque, efficiency, and harmonics are investigated. The graphics and the tables are obtained sequentially for each skew length. The skew rate is selected as 0.5 on the table to get a required performance in prototype manufacturing. Therefore, it makes the motor performance higher and reduce the torque ripple, vibration, and acoustic noise. The designed PMSM will be used to carry the elevator cabin between the floors. Due to centrifugal force, the PM motors are usually designed as inset magnet in rotor side. On the contrary in this study, the PMs are mounted on the surface of the rotor because of the low speed. All of the designs are confirmed by using the CD-Adapco Speed software based on Finite Element Method (FEM).
Keywords: Permanent magnet synchronous motor; Cogging torque; Skew; CD-adapco speed; Torque ripple